A Summary of Medical Students' Preference for Healthy Campus Canteen Menus - Farhan, Muhammad; Kurniati, Ardesy Melizah; Liberty, Iche Andriyani; Husin, Syarif; Lestari, Hertanti Indah (Universitas Teuku Umar, 2022)
The canteen is one of the supporting facilities on campus. The availability of nutritious menus is of great assistance in meeting the nutritional needs of the academic community in support of its learning activities. However, not all campus canteens meet the criteria for healthy canteens. Students' input is required for the establishment of a healthy canteen, especially regarding the menu. This study aims to explore the canteen menu preferences of medical students at Universitas Sriwijaya to develop a healthy canteen. This study is an observational survey, and Google Form is used to collect data through an online questionnaire. The majority of the 646 samples (72.4 %) were females, lived within the family house (52.8 %), had meals from the canteen (70.1 %), were likely to buy ready-to-eat food (65 %), and spent their daily pocket money between IDR 20,000 to 30,000 (34.1 %). A part of them was pleased with the former canteen's menu, including flavor, presentation, menu variants, accessibility to desired menus, pricing, and nutrition content. The majority of students prefer to purchase the main menu (85.1 %), drink without added sugar (74.8%), get the seller's predetermined food portion (54%), and select a canteen that regulates unhealthy menu limitations (46.9 %), which provides a complete menu list with prices and nutritional content (49.8 %). Most students prefer menus that fill them up, no added sugar drinks, predetermined menu portions, limiting menus that are considered unhealthy, and clear nutritional content and price information on the menu list.